A pterodactyloid pterosaur from the Upper Cretaceous Lapurr sandstone, West Turkana, Kenya - O'Connor,Patrick M. (2011)
An isolated pterosaurian caudal cervical (~ postcervical) vertebra was recovered from the Upper Cretaceous Lapurr sandstone ofWest Turkana, northwestern Kenya. The vertebral centrum is short, wide, and dorsoventrally compressed. Although the specimen is lightly built similar to most pterosaurs, it is here referred to Pterodactyloidea and tentatively to the Azhdarchidae in that it lacks pneumatic features on both the centrum and neural arch. This represents one of the few pterosaurs recovered from the entirety of Afro-Arabia, the first pterosaur recovered from the Cretaceous of East Africa, and, significantly, a specimen that was recovered from fluvial deposits rather than the near-shore marine setting typical of most pterosaur discoveries.